Differentiation of vascular smooth muscle cells from local precursors during embryonic and adult arteriogenesis requires Notch signaling - Chang, Linda (National Academy of Sciences, 2012)
Vascular smooth muscle cells (VSMC) have been suggested to arise from various developmental sources during embryogenesis, depending on the vascular bed. However, evidence also points to a common subpopulation of vascular progenitor cells predisposed to VSMC fate in the embryo. In the present study, we use binary transgenic reporter mice to identify a Tie1(+)CD31(dim)vascular endothelial (VE)-cadherin(−)CD45(−) precursor that gives rise to VSMC in vivo in all vascular beds examined. This precursor does not represent a mature endothelial cell, because a VE-cadherin promoter-driven reporter shows no expression in VSMC during murine development. Blockade of Notch signaling in the Tie1(+) precursor cell, but not the VE-cadherin(+) endothelial cell, decreases VSMC investment of developing arteries, leading to localized hemorrhage in the embryo at the time of vascular maturation. However, Notch signaling is not required in the Tie1(+) precursor after establishment of a stable artery. Thus, Notch activity is required in the differentiation of a Tie1(+) local precursor to VSMC in a spatiotemporal fashion across all vascular beds.